The Cloud over My Head and Other Stories: Children’s Picture Books on Children’s Anxiety - Regina Carissa Rachman (Institute of Research and Community Outreach - Petra Christian University, 2021)
This creative work is in five children’s picture book format for the target of age five to nine and the topic focuses on children’s anxiety. My stories will be in low fantasy genre, where the anxiety in each story has various forms. The main theme of my stories is to show that what anxiety produces negative thoughts that are not based on reality. To show how children can have anxiety, I use Cognitive Distortions theory, and to show how children can cope with their anxieties, I use Cognitive Behavioural Therapy (CBT) theory. Each of my stories will be about how anxiety happens to the main character and how the main character solves the problem. From the research I did, I found that anxiety happens to children and it produces negative thoughts that are later proven to be untrue. With CBT, children can also learn how to cope their anxieties by self-monitoring their own emotions and turn negative thoughts into positive ones. Keywords: Children, anxiety, cognitive distortions, cognitive behavioural therapy